(untitled) (Faridpur Medical College Journal, 2025)
Breast abscesses are a common and often painful condition that primarily affects women, particularly during the lactating years, although they can occur in non-lactating women as well. The management of breast abscesses involves a combination of conservative measures, antibiotics, and, in many cases, surgical interventions such as incision and drainage. This study aims to explore the clinical characteristics, microbiological findings, and treatment strategies for breast abscesses patients. This cross-sectional type of observational study was conducted in Department of Surgery, Dhaka Medical College Hospital from August 2016 to February 2017. A total of 60 patients were selected as study subjects using purposive sampling technique. Among them the highest incidence in the 21–30 years age group (43.33%) and 36.67% in the 11–20 years group. Most patients were married (73.33%), housewives (73.33%), and from a poor socioeconomic background (70%). The common symptoms included pain, fever, swelling, and redness (86.67%), and 10% had recurrent abscesses. Nipple abnormalities were found in 10% of cases. Staphylococcus aureus was isolated in 76.67% of cases, all sensitive to Flucloxacillin. Treatment was primarily incision and drainage (86.67%), with a small percentage requiring mastectomy, quadrantectomy, or conservative management. Incision and drainage remains the primary treatment for recent breast abscesses (86.67%), while fewer cases required mastectomy (6.67%), quadrantectomy (3.33%), or conservative management (3.33%). A tailored treatment strategy is essential for optimizing patient outcomes. Faridpur Med. Coll. J. 2025;20(2):39-43